REPRESENTATION OF IDEOLOGY IN INDONESIAN PROGRAMS LAWYER CLUB (ILC) tvOne BASED ON MICROSTRUCTURE ANALYSIS OF CRITICAL DISCOURSE MODEL TEUN A. VAN DIJK: REPRESENTASI IDEOLOGI DALAM PROGRAM INDONESIA LAWYER CLUB (ILC) tvOne BERDASARKAN STRUKTUR MIKRO ANALISIS WACANA KRITIS MODEL TEUN A. VAN DIJK - Muhammad Kasir (LLDIKTI Wilayah X, 2021)
The problem formulation in this study is how is the Representation of Ideology in tvOne's Indonesia Lawyer Club (ILC) Program based on the microstructure of critical discourse analysis model Teun A. van Dijk?. The purpose of this research is to describe the Representation of Ideology in the Program Indonesia Lawyer Club (ILC) tvOne based on the microstructure of the analysis of the discourse ktiris Model Teun A. van Dijk. The method used is descriptive research method with qualitative approach. This research data is the speeches of speakers in the talk show Program Indonesia Lawyer Club episode 03 December 2019 with the theme